Design of thermoresponsive poly(ionic liquid) gels containing proline units to catalyse aldol reaction in water. (3rd January 2018) - Okafuji, Akiyoshi; Kohno, Yuki; Nakamura, Nobuhumi; Ohno, Hiroyuki
Abstract: Ionic liquid monomers and a proline-containing monomer were copolymerised in the presence of cross-linker to form ionic liquid polymer gels that show lower critical solution temperature-type phase change in water. The obtained gels were utilised as catalysts for aldol reaction in water. Since proline-catalysed aldol reaction is composed of three equilibrium steps including dehydration condensation reaction and hydrolysis reaction, yield of product was affected by the water content around the proline unit in the gel. Since thus prepared ionic liquid polymer gels showed the thermo-responsive change in water content, the product yield was found to be affected by the temperature around the phase transition temperature. Graphical abstract: Image 1 Highlights: Thermo-responsive ionic liquids were copolymerised with proline monomer. The hydration degree of the gels depended on temperature. Proline catalysed aldol reaction was affected by water content. The catalytic reaction in this gel can be controlled by temperature.